ChemInform Abstract: Thiazolidinedione—Isatin Conjugates via an Uncatalyzed Diastereoselective Aldol Reaction on Water. Issue 29 (22nd July 2014) - Paladhi, Sushovan; Bhati, Meeta; Panda, Deepanjan; Dash, Jyotirmayee
Abstract The title conjugates are obtained in excellent yields and diastereoselectivities.